PENGARUH KUALITAS INFORMASI TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI MANAJEMEN REKAM MEDIS DI RS PARU RESPIRA YOGYAKARTA - Ivan Tinarbudi Gavinov; Nursavitri Widyaningrum Maswatu; Parmadi Sigit Purnomo (LPPM Akademi Manajemen Administrasi Yogyakarta, 2024)
Background: The development of technology and information systems has experienced very rapid development. Information systems are currently very much needed by organizations, companies and respondents to obtain convenience, speed and accuracy in processing and obtaining data and/or information. Respira Lung Hospital has a system that sometimes goes down erratically several times, taking around 30 seconds or even up to several hours, this down system will switch to manual for backup. However, because there is no net work backup which is caused by the local network, or from the Ministry of Communication and Information and from overloaded hosting conditions, this hampers employee services. So regarding existing problems and the hardware, it can be upgraded to overcome the problem if you update the latest version of SIM-RM. Objective: To determine the influence of information quality on user satisfaction of the medical record management information system at Respira Pulmonary Hospital Yogyakarta. Method: This type of research uses quantitative methods with a cross sectional design. The research sample was 80 using purposive sampling technique. Data analysis uses Kendall's Tau. Results: The research results show that there is a significant influence between the variables system quality, information quality, and service quality on user satisfaction of the medical record management information system at Respira Lung Hospital, Yogyakarta. With the most dominant variable, namely the quality of information on user satisfaction of the medical record management information system at Respira Pulmonary Hospital, Yogyakarta. Conclusion: There is a significant influence between system quality, information quality and service quality on user satisfaction of the medical record management information system. With the most dominant variable, namely the quality of information on user satisfaction of the medical record management information system at Respira Pulmonary Hospital, Yogyakarta.